Seeking balance: Professional development needs of tenured information science faculty. Issue 1 (24th October 2017) - Lopatovska, Irene; O'Brien, Heather; Rorissa, Abebe; Ivanović, Martina Dragija; Julien, Heidi
ABSTRACT: There is minimal, mainly anecdotal, evidence of discourse about the professional development of information science (IS) academics. In an effort to initiate discussion on professional development and encourage information sharing among IS faculty and administrators, we organized a panel at the 2016 Annual Meeting of ASIS&T (Lopatovska et al., 2016 ). The panel brought attention to the professional development resources and strategies available to mid‐career faculty and uncovered the need to continue the discussion. This proposed interactive panel aims to identify tenured IS faculty members' needs related to their scholarly, teaching and service pursuits, explore professional wellbeing and work climate, share best practices and brainstorm potential solutions for some of the identified issues. The issues and solutions uncovered during the panel discussion will be shared with the broader community with the hope that recommendations can be adopted and acted upon by individuals, academic institutions and professional associations. The panel will be of interest to faculty, doctoral students and academic administrators.